IMPLEMENTASI KEBIJAKAN SERTIFIKASI KOMPETENSI SUMBER DAYA MANUSIA (SDM) PARIWISATA DI ERA MASYARAKAT EKONOMI ASEAN (Studi Kasus di Dinas Sosial Tenaga Kerja Kabupaten Badung) - Chandra, Daima Oshika; Noak, Dr. Piers Andreas; Supriliyani, Ni Wayan (CITIZEN CHARTER, 2017)
ABSTRACT The problems of policy implementation of human resource competence certification Human Resources (HR) Tourism in the era of the ASEAN Economic Community (AEC) in the realizing of the program has not been implemented, that problem must beovercome. In practice, the implementation of policy is a dynamic process so that in the end will get a result in accordance with the goals or target of the policy itself. The regional Government policy for tourism to support the ASEAN Economic Community (AEC) is to increase knowledge and skills (competencies) for perpetrators of tourism for the fulfillment of the standardization of services and tourist management through competency test.This research uses a qualitative method with descriptive approach. The data obtained by the authors by making observation to be able to see directly the phenomena that occurred in the field and conduct in-depth interviews with informants related to the implementation of HR competency certification policy in the era of the MEA. The conclusion of this research is, first the implementation of HR certification policy era of tourism in the MEA is not optimal in the implementation. Second, the benefits of the certification of tourism human resources competence in the era of MEA has not been felt. The implication of this research is that the policy of the policy of certification of human resource competence (HR) Tourism in the era of the ASEAN Economic Community (AEC) should be increased in order to realize the program to be implemented and the expected goal is achieved Keywords: Policy Implementation, Certification of human resource competency (HR) Tourism, the ASEAN Economic Community (AEC).